PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO DAN WORDWALL DALAM MENINGKATKAN KONSENTRASI SISWA MATERI BANI ABBASYIAH MTS TERPADU BERKAH PALANGKA RAYA - Abdul Aziz; Andin Muhamad Maulana; Husnul Khatimah; Yusika Amelia Putri (CV. ADIBA AISHA AMIRA, 2024)
Technology provides various alternative learning methods, such as videos, animations, simulations, and educational games, which make learning more interesting and interactive. This study aims to develop video-based learning media and wordwall educational quizzes to improve students' concentration on Bani Abbasiyah material at MTs Terpadu Berkah Palangka Raya. The research method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation) which consists of five stages, namely needs analysis, media design, development, implementation, and effectiveness evaluation. The results of the analysis show that students find it difficult to concentrate when the teacher explains the learning material. Therefore, interactive media is needed to improve concentration and understanding so that students are interested in the material presented. At the development stage, we will create learning media in the form of visualization videos of Bani Abbasiyah material, as well as wordwall-based quizzes to increase student participation. The trial of the development of this learning media was carried out in one meeting and learning was delivered to students using the developed media. Video and wordwall- based media have proven successful and received positive responses from students because they can increase interest in learning and active participation in the learning process. This study concludes that the results are quite satisfactory in improving concentration and focus in students because the results of the questionnaire obtained students feel interested and enthusiastic about the media provided which indirectly makes them focus on the video. Therefore, video-based learning media and wordwalls can be an effective alternative to improve students' concentration and understanding of the subject of Islamic Cultural History, especially in the Bani Abbasiyah material.